The Fate of the Superior Mesenteric Artery in Fenestrated Endovascular Repair of Complex Abdominal Aortic Aneurysms - Yongcheng Xu (Radcliffe Medical Media, 2019)
Issues related to the superior mesenteric artery (SMA) in fenestrated endovascular aortic aneurysm repair (f-EVAR), such as misalignment of the endograft and bridging devices-associated complications, are rarely reported. Moreover, the absence of autopsies in the majority of patients who died in the published series makes a possible correlation with occlusion of the SMA unknown. Current studies that reported on f-EVAR were reviewed accordingly, aiming to improve our understanding of the natural course of the SMA in fenestrated technology and to explore the associated clinical complications.